Efficacy and safety of Ginkgolide with intravenous alteplase thrombolysis in acute ischemic stroke with large vessel occlusion: a subgroup analysis of GIANT - Zhang, Zheyu; Zhong, Wansi; Zhang, Xuting; Ma, Xiaodong; Lu, Xudong; Zhang, Meixia; Tao, Anyang; Zhang, Bing; Lou, Min (Frontiers in Pharmacology, 2024)
Aim This study aims to explore the effectiveness and safety of Ginkgolide® in acute ischemic stroke (AIS) patients with large vessel occlusion (LVO) and moderate-to-severe stroke receiving intravenous alteplase thrombolysis (IVT). Methods Ginkgolide with Intravenous Alteplase Thrombolysis in Acute Ischemic Stroke Improving Neurological Function (GIANT) was an open-label, prospective, multicenter, cluster-randomized clinical trial and included AIS patients in 24 centers randomized to the intervention of intravenous Ginkgolide® or control group within the first 24 h after IVT. LVO was defined as any occlusion of the internal carotid artery, M1 or M2 of the middle cerebral artery, A1 or A2 of the anterior cerebral artery, P1 of the posterior cerebral artery, and V4 of the vertebral artery or the basilar artery. Stroke severity was assessed with the National Institutes of Health Stroke Scale (minor ≤5; moderate-to-severe >5). The primary outcome was a good outcome, defined as a modified Rankin Scale (mRS) score of 0–2 at 90 days. Secondary outcomes were early neurological improvement (ENI), defined as ≥18% increase in the National Institutes of Health Stroke Scale (NIHSS) score at 7 days compared to baseline and distribution of mRS at 3 months. Results A total of 1,113 patients were included, with 268/913 (29.4%) presenting LVO and 508 (45.6%) presenting moderate-to-severe stroke. In patients with LVO, Ginkgolide® usage was independently associated with ENI (P = 0.001) but not with a good outcome (P = 0.154). In the moderate-to-severe stroke subgroup, Ginkgolide® was independently associated with both a good outcome (P = 0.009) and ENI (P = 0.028). Ginkgolide® did not increase the risk of hemorrhagic transformation (all P > 0.05). Conclusion Using Ginkgolide® within 24-h after intravenous rt-PA is effective and safe in LVO and moderate-to-severe stroke patients.